Implementasi Prinsip Tanggung Jawab Bersama tapi Beda (Common But Difeerentiated Responsibility) dalam Protokol Kyoto - Sri Wartini (Jurnal Hukum IUS QUIA IUSTUM, 2007)
Common but Differentiated responsibility is one of the principles which has been adopted in the Kyoto Protocol. Common but differentiated responsibility requires us to recognize that because of historical circumstances, countries at different stages of development have different capacities, and consequently different levels of kind of responsibility for dealing with international environmental issues.  Implicit in this dichotomization is the notion that developing countries lack sufficient technical expertise, regulatory and administrative efficacy, and economic capability to reduce green house gases.  The Implementaion of  common but differentiated responsibility principle under the Kyoto Protocol embodys in three flexible mechanisms. These mechanism include emission trading, joint implementation, and clean development mechanism. To maintain the broader participation from develop and developing countries the Implementaion of  common but differentiated responsibility principle should be based on equity principle.  However, without the participation of the United States to the Kyoto Protocol mechanisms cause the implementation of the protocol less effective because the United States is the biggest emitter in the world.